Tinjauan Sistematis Hubungan Perilaku Sanitasi Lingkungan Masyarakat Dengan Kejadian Penyakit Diare di Wilayah Pesisir - Susilawati susilawati; Nurul Izmi Syarifah Margolang Izmi (Publikasi Indonesia, 2022)
Diarrhea is a disease caused by bacteria that attack the digestive organs. The causes of diarrheal disease are very diverse, ranging from people's consumption patterns, water quality, sanitation behavior and so on. Research on the causes of diarrheal disease has been developed so that it leads to a conclusion that diarrheal disease is caused by things that are dirty and contain bacteria. Therefore, this study was conducted to determine the relationship between sanitation and diarrhea aimed at coastal communities. The data taken in this study is a study of literature from several related journals and the retrieval of data obtained from the results of previous studies. Some of the data taken will be processed and a conclusion will be drawn so that it will know that people's behavior about sanitation will greatly affect diarrheal disease. So, this research will also explain about the behavior of the community which has an impact on the number of cases of diarrheal disease that occurs in coastal communities. The data is taken from data on the number of cases of diarrheal disease, index data on sanitation quality, and community behavior. The data obtained from the number of cases of diarrheal disease will be compared with the sanitation quality index data. In this regard, the behavior of the community is also a consideration. So the conclusions drawn from the data will be more accurate. The processed data also considers several other components that affect the dependent variable. The components are components that are free and are considered conditionally or if any. If in an area there are components in question, the calculation of the data will also be affected. The research object of this journal is to focus on coastal communities because they are the people who interact the most with water compared to residents in other places, even people who live near rivers.